2003
DOI: 10.1093/qjmed/hcg128
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral infarction in perinatal and childhood bacterial meningitis

Abstract: There was a high prevalence of cerebral infarctions when the disease was caused by S. pneumoniae and Salmonella species. Occurrence was highest in the first year of life, and the prognosis in this patient group is poor. Risk factors associated with cerebral infarction in our patients included age 28-365 days, seizures, hydrocephalus, disturbed consciousness on admission, and high CSF lactate concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 22 publications
1
28
1
1
Order By: Relevance
“…21 In the past, H influenzae type b has been an important cause of meningitis associated with a greater mortality (25%) than other bacterial meningitis, particularly when complicated with cerebral infarction 22 ; however, in countries in which the conjugate vaccine is used routinely, H influenzae meningitis has essentially disappeared. 21 Chang et al 19 identified S pneumoniae and Salmonella species as the most common causes in children sustaining bacterial meningitis and cerebral infarction within the first year of life. Salih et al 23 reported that H influenzae, S pneumoniae, and S aureus were the most frequent causes of meningitis with subsequent cerebral infarction in Saudi Arabian children age 5-21 months.…”
Section: Meningoencephalitides Complicated With Infectious Vasculitismentioning
confidence: 99%
“…21 In the past, H influenzae type b has been an important cause of meningitis associated with a greater mortality (25%) than other bacterial meningitis, particularly when complicated with cerebral infarction 22 ; however, in countries in which the conjugate vaccine is used routinely, H influenzae meningitis has essentially disappeared. 21 Chang et al 19 identified S pneumoniae and Salmonella species as the most common causes in children sustaining bacterial meningitis and cerebral infarction within the first year of life. Salih et al 23 reported that H influenzae, S pneumoniae, and S aureus were the most frequent causes of meningitis with subsequent cerebral infarction in Saudi Arabian children age 5-21 months.…”
Section: Meningoencephalitides Complicated With Infectious Vasculitismentioning
confidence: 99%
“…Arterial ischemic stroke, CSVT, and intracranial hemorrhage are all known complications of pneumococcal meningitis in children 1,[13][14][15] and in adults, 18 and portend a worse prognosis. 16,17 Our 2 cases of vaccinated children with pneumococcal meningitis due to non-PCV13 serotypes highlight its spectrum of cerebrovascular disease and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Stroke and meningitis are frequently comorbid; before the introduction of PCV7, strokes were discovered in 10% to 27% of children with acute bacterial meningitis. [13][14][15] Some small studies suggest S pneumoniae infection is more commonly associated with stroke relative to other pathogens, 13,15 although others found no association.…”
mentioning
confidence: 99%
“…Strokes in children also result in significant morbidity as > 50% of survivors will have cognitive or motor disabilities [2,3]. Little attention has been paid to strokes that occur in children who are already critically ill. Serious systemic illnesses, such as meningitis and underlying malignancy, are well-known risk factors for stroke in childhood [4,5]. We hypothesized that mortality among pediatric stroke patients increases when critical illness precedes stroke.…”
Section: Introductionmentioning
confidence: 99%